Engagement of signaling pathways of protease‐activated receptor 2 and μ‐opioid receptor in bone cancer pain and morphine tolerance. Issue 6 (10th March 2015) - Bao, Yanju; Gao, Yebo; Hou, Wei; Yang, Liping; Kong, Xiangying; Zheng, Honggang; Li, Conghuang; Hua, Baojin
<x xml:space="preserve">Abstract</x> Pain is one of the most common and distressing symptoms suffered by patients with progression of cancer. Using a rat model of bone cancer, recent findings suggest that proteinase‐activated receptor 2 (PAR2) signaling pathways contribute to neuropathic pain and blocking PAR2 amplifies antinociceptive effects of systemic morphine. The purpose of our study was to examine the underlying mechanisms responsible for the role of PAR2 in regulating bone cancer‐evoked pain and the tolerance of systemic morphine. Breast sarcocarcinoma Walker 256 cells were implanted into the tibia bone cavity of rats and this evoked significant mechanical and thermal hyperalgesia. Our results showed that the protein expression of PAR2 and its downstream pathways (protein kinases namely, PKCε and PKA) and transient receptor potential vanilloid 1 (TRPV1) were amplified in the dorsal horn of the spinal cord of bone cancer rats compared to control rats. Blocking spinal PAR2 by using FSLLRY‐NH2 significantly attenuated the activities of PKCε/PKA signaling pathways and TRPV1 expression as well as mechanical and thermal hyperalgesia. Also, inhibition of PKCε/PKA and TRPV1 significantly diminished the hyperalgesia observed in bone cancer rats. Additionally, blocking PAR2 enhanced the attenuations of PKCε/PKA and cyclic adenosine monophosphate induced by morphine and further extended analgesia of morphine via μ‐opioid receptor (MOR). Our data revealed specific signaling pathways, leading to bone cancer pain, including the activation of PAR2, downstream PKCε/PKA, TRPV1 and resultant sensitization of MOR. Targeting one or more of these signaling molecules may present new opportunities for treatment and management of bone cancer pain often observed in clinics.